Cotidiano de cuidado da equipe de enfermagem às crianças com necessidades especiais de saúde hospitalizadas e suas famílias - Zamberlan, Kellen Cervo (2014)
Children with special healthcare needs (CSHCN) represent an emerging clientele in health services, especially in the hospital environment. Professionals should be prepared to act in this reality, since these children are increasingly involved in their everyday care. Thus, this study aimed to know the conception of the nursing staff about children with special health care needs of a pediatric inpatient unit; describing the everyday care of the nursing staff of a pediatric inpatient unit facing these children and their families; analyze the limits and possibilities that permeate everyday care of the nursing staff, living with children with special health care needs and their families in the context of pediatric hospitalization. This is a qualitative research that was conducted with the nursing staff of the pediatric unit of a teaching hospital; including 13 participants in the research. The data production occurred through the sensitive creative method, with the realization of the dynamics of creativity and sensitivity: Storm Creative, Sewing Stories and Almanac associated with participant observation in the hospital unit during April-June 2013. Data were submitted to analysis of discourse in its French stream. The research was approved by Ethical Committee under number: 12142612.8.0000.5346, according to Brazilian Resolution No. 466/2012. The results pointed out that the conception about child with special healthcare needs for professional nursing team, generally, refers to children who have neurological disorders. The everyday care of this team presents limitations such as lack of material resources; difficulties to solving problems and suffering of the team face of the obstacles experienced by the children and their families, plus the lack of multidisciplinary work. The possibilities were related to inclusion of family in the caring to child; family togetherness, and the solidarity of nursing team. The living with CSHCN and their families, made the staff to be positioned in defense of them. It is concluded that the everyday care front of CSHCN in hospital settings is still permeated with shadow aspects that permeate the practice of nursing staff as the invisibility of the all particularities of the CSCHN group, and the attempt to move away from these during anguish periods of the staff and family as well. However, many of these aspects are in the light and some also surfaced during the collective debate in the group space that was highlight by participants in a dialectic movement between the suffering and happiness in the CSCHN caring.